Prevalence of prediabetes and associated factors among community members in rural Isingiro district - Isaac Petit Ampeire; Peter Chris Kawugezi; Edgar Mugema Mulogo (BMC, 2023)
Abstract Background In rural Uganda a significant number of persons afflicted with pre-diabetes are unaware of the condition. This is likely to lead to diabetic complications resulting in catastrophic health expendirure.The burden of prediabetes in rural Isingiro has not previously been determined. This study examined the prevalence of prediabetes and the associated factors among rural community members. Methods We conducted a cross-sectional survey and enrolled 370 participants aged between 18 and 70 years in the Kabuyanda sub-county, rural Isingiro district in march 2021. Multistage sampling and systematic random sampling were conducted to select eligible households. Data was collected using a pretested WHO STEP-wise protocol questionnaire. The primary outcome was prediabetes (FBG = 6.1mmol/l to 6.9mmol/l), calculated as a proportion. Participants known to be diabetic or on medication were excluded. Chi-square tests and multivariate logistic regression model were performed for data analysis using STATA. Results The prevalence of prediabetes was 9.19% (95% CI 6.23-12.14). Independent factors significantly associated with pre-diabetes were; advancing age [AOR = 5.7, 95% CI:1.03-32.30], moderate-intensity work [AOR = 2.6,95% CI:1.23-5.63], high level of consumption of a healthy diet [AOR = 5.7, 95% CI:1.67-19.05] and body mass index [AOR = 3.7, 95% CI:1.41-9.20]. Conclusion Prediabetes is prevalent among adult community members in rural Isingiro, southwestern Uganda. Age and lifestyle factors predict prediabetes in this rural population, suggesting a need for targeted health promotion interventions.